Importance of second‐look endoscopy after per‐oral endoscopic myotomy for safe postoperative management. Issue 3 (2nd September 2020) - Fujiyoshi, Yusuke; Inoue, Haruhiro; Abad, Mary Raina Angeli; Rodriguez de Santiago, Enrique; Nishikawa, Yohei; Sakaguchi, Takuki; Toshimori, Akiko; Shimamura, Yuto; Tanabe, Mayo; Sumi, Kazuya; Kimura, Ryusuke; Izawa, Shinya; et al.
Abstract : Objectives: Per‐oral endoscopic myotomy (POEM) is a safe and effective treatment for achalasia and esophageal motility disorders. The role of second‐look endoscopy (SE) on postoperative day 1 has not been examined. This study aimed to evaluate the findings and need of SE after POEM. Methods: This is a single‐center, retrospective study. All consecutive patients who underwent POEM and SE on postoperative day 1 between December 2017 and September 2019 were included. The primary endpoint was the rate of newly‐detected adverse events (nAE) during SE that required endoscopic intervention or deviation from the normal postoperative course. Multivariate logistic regression was used to identify predictors of nAE. Results: Four‐hundred‐ninety‐seven patients (mean age, 50.3 years; female, 49.9%) were included. SE identified abnormal findings in a total of 71 patients (14.3%). nAE which required endoscopic intervention or deviation from the normal postoperative course were identified in 12 patients (2.4%): eight (1.6%) entry site dehiscence; two (0.4%) submucosal hemorrhage or hematoma; and two (0.4%) dehiscence of an intraoperative perforation site after endoclip closure. Other findings such as mucosal thermal damage without perforation and small submucosal hematoma were found in 54 patients (10.9%) and five patients (1.0%), respectively. Multivariate analysis showed that longer operation time and intraoperative adverse events (AE) were associated with clinically significant nAE during SE. Conclusions: Second‐look endoscopy can detect and treat nAE that may lead to severe AE. Thus, SE should be highly considered before starting oral ingestion in all cases, and especially in those who present an intraoperative AE and longer operation time.